An integrated approach to character education - 4 0 16; Rusnak, Timothy; 5 (Thousand Oaks, California : Corwin Press, 1998)
Offers teachers an action-oriented way of addressing students' values and character growth, emphasizing the combination of three vital aspects of teaching and learning, thinking, feeling, and acting.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Study and teaching;Study and teaching.;Administration -- Moral education;Character;Curriculum planning;Active learning;Classroom environment;Community and school;School management and organization;Character;Active learning.;Classroom environment.;Schools -- United States.;United States.;United States.;United States.;United States.;United States.;United States.;United States; 20; 2